Truman [videorecording (DVD)] - Grubin, David; Robards, Jason (PBS Home Video ; Distributed by Paramount Home Entertainment, 2008)
The story of the unlikely rise of a gritty American original, Harry Truman. He was a farmer, a bankrupt businessman, an unknown politician from Missouri who suddenly found himself president. Of all the men who had held America's highest office, Harry Truman was the least prepared, but he would prove to be a surprise. Facing some of the biggest crises of the century, Truman would end the war with Germany, use the atomic bomb against Japan, confront an expanding Soviet Union and wage war in Korea-all while the woman he adored, his wife Bess, refused to stay in the White House and play the role of First Lady.